Labor Market Concentration and Competition Policy across the Atlantic - Satoshi Araki; Andrea Bassanini; Andrew Green; Luca Marcolin; Cristina Volpin (Institute of Labor Economics (IZA), 2022)
Drawing upon data from the largest cross-country study of labor market concentration to date, this paper analyzes the level of concentration of labor input markets in Europe and North America and provides a comparative perspective on employers' monopsony power. It explores the characteristics of monopsony in labor markets and documents its impact by looking at the magnitude of employer concentration in selected jurisdictions. Using a harmonized dataset of online vacancies, this paper shows that European labor markets are no more competitive than North American ones. It also supports the view that the effects of concentration on labor markets are broadly similar in both Europe and North America, despite the much stronger labor market institutions in Europe. The article shows that there is no apparent economic or legal justification for a lack of enforcement activity by European competition authorities in labor markets relative to the US. While enforcement action has picked up in the last two years in Europe, there is likely still scope for a significant increase in the role of competition enforcement in labor markets. The article identifies sectors and practices that may be scrutinized with priority by European competition authorities and proposes a mix of enforcement, merger control and well-targeted policy and regulatory solutions to address employers' monopsony power.
Keywords: J31; J41; J42; L40; 330; labour market concentration; monopsony; cross-country comparison; competition enforcement